2009
DOI: 10.1111/j.1095-8649.2009.02296.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the swimbladder parasite Anguillicola crassus on the migration of European silver eels Anguilla anguilla in the Baltic Sea

Abstract: In a mark-recapture study in 2006, migrating European Anguilla anguilla silver eels were caught, tagged and released in the Baltic Sea and recaptures in commercial pound nets examined for possible effects on migration of infection with the swimbladder parasite Anguillicola crassus. The overall recapture rate was 36%. The prevalence of infection was lowest at the northernmost sampling site. There were no significant differences between infected and uninfected A. anguilla in condition indices, body fat content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 33 publications
4
54
0
Order By: Relevance
“…Following this argument, we propose here a general integrative scenario to account for the known A. crassus effects and the peculiarity of eel hosts. On the one hand, it has been shown that severely affected eels die first in a stressful environment [55,56], and are more likely to get caught [57,58]. On the other hand, the panmictic nature of eel reproduction [59] generates high inter-individual genetic variability, precludes local adaptation and favours phenotypic plasticity [60].…”
Section: Discussionmentioning
confidence: 99%
“…Following this argument, we propose here a general integrative scenario to account for the known A. crassus effects and the peculiarity of eel hosts. On the one hand, it has been shown that severely affected eels die first in a stressful environment [55,56], and are more likely to get caught [57,58]. On the other hand, the panmictic nature of eel reproduction [59] generates high inter-individual genetic variability, precludes local adaptation and favours phenotypic plasticity [60].…”
Section: Discussionmentioning
confidence: 99%
“…However, available data suggests this may not typically be the case in the eastern Mediterranean; Vistonis Lake eels were all large females (905 mm mean body length), as were those from the nearby River Nestos in Greece (656 mm mean body length in 2008; Koutrakis et al, unpublished data) and from the Göksu Delta, Turkey (729 mm mean body length between 2007 and 2010; Rad et al, 2013). The majority (>95%) of eels examined from Vistonis Lake were classified as silver-stage migrants according to established indices (Pankhurst, 1982;Durif et al, 2005;Durif et al, 2009a), and their condition factor exceeded that of female silver eels from French Atlantic drainages (Durif et al, 2005) and the Baltic Sea (Sjöberg et al, 2009). Inferences from artificial maturation trials suggest that these characteristics (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The invasive nematode A. crassus causes damage to the swimbaldder, which may manifest itself during the oceanic migration, meaning infected silver eels may not be able to reach the spawning ground or contribute to reproduction (Palstra et al, 2007;Sjöberg et al, 2009). Anguillicola crassus was first reported from Greece as early as 1988 (Moravec, 1992) and is now found throughout much of the eastern Mediterranean.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study using otolith microchemistry, Martin et al (2010) found significant differences in trace element signatures between glass eels/ elvers collected in European locations and leptocephali caught in the Sargasso Sea, suggesting that the former were born in a spawn- ing site linked to favourable transport and/or feeding conditions, while the latter may have been sampled in a less favourable region in the Sargasso Sea, with a low probability of reaching continental growth areas. Perturbation of the spawning success might be exacerbated by the detrimental effects of continental factors such as pollution or parasites leading to a reduced fitness and/or fecundity of spawners (Palstra et al, 2006;Sjoberg et al, 2009). …”
Section: Oceanic Influence On Adultsmentioning
confidence: 99%